2021
DOI: 10.1016/j.sleep.2020.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disruption and duration are associated with variants in genes involved in energy homeostasis in adults with HIV/AIDS

Abstract: Objective: To determine whether selected genes and plasma markers involved in energy homeostasis are associated with sleep disruption or duration in adults with HIV/AIDS. Methods: A sample of 289 adults with HIV/AIDS wore a wrist actigraph for 72 hours to estimate total sleep time (TST) and wake after sleep onset (WASO). Twenty-three single nucleotide polymorphisms (SNP) spanning 5 energy homeostasis genes (adiponectin [ADIPOQ], ghrelin [GHRL], leptin [LEP], peroxisome proliferator-activated receptor-alpha [PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…According to Alikhani et al (2020) , Chen et al (2021) , Daubert et al (2022) , Han et al (2021) , Ren et al (2018) , Wang et al (2021) , and Yan et al (2021) , psychological factors, such as depression, anxiety, and stress-related to living with a chronic illness, preceded sleep disturbance in PLWH. The second antecedent of sleep disturbance involves biological factors, including low CD4 cell levels ( Shi et al, 2020 ), high viral load ( Balthazar et al, 2021a ), genetic involvement ( Aouizerat et al, 2021 ; Ding et al, 2018 ), sex ( De Francesco et al, 2021a ; Moore et al, 2020 ), brain damage ( Happe, 2020 ; Leone et al, 2021 ), disease progress and duration ( Faraut et al, 2018b ; Milinkovic et al, 2020 ), and decreased immune function ( Babson et al, 2013 ; Low et al, 2012 ; Taibi et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Alikhani et al (2020) , Chen et al (2021) , Daubert et al (2022) , Han et al (2021) , Ren et al (2018) , Wang et al (2021) , and Yan et al (2021) , psychological factors, such as depression, anxiety, and stress-related to living with a chronic illness, preceded sleep disturbance in PLWH. The second antecedent of sleep disturbance involves biological factors, including low CD4 cell levels ( Shi et al, 2020 ), high viral load ( Balthazar et al, 2021a ), genetic involvement ( Aouizerat et al, 2021 ; Ding et al, 2018 ), sex ( De Francesco et al, 2021a ; Moore et al, 2020 ), brain damage ( Happe, 2020 ; Leone et al, 2021 ), disease progress and duration ( Faraut et al, 2018b ; Milinkovic et al, 2020 ), and decreased immune function ( Babson et al, 2013 ; Low et al, 2012 ; Taibi et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, identifying the concept's attributes is the primary goal of the concept analysis (Rodgers, 2000). In this analysis, two main attributes of sleep disturbance in the context of HIV were identified: a) subjective measures, including reduced total sleep (Aouizerat et al, 2021;dos Santos et al, 2018;Faraut et al, 2018aFaraut et al, , 2021Hixon et al, 2020;Santos et al, 2018), difficulty falling asleep, nighttime and early morning awakenings, feeling sleepy and poorly rested after a night's sleep, frequent arousal, and irritability (American Academy of Sleep Medicine, 2014a), and b) objective measures, including changes in sleep architecture and sleep continuity (Shikuma et al, 2018). During the analysis, it was found that only a few authors explicitly defined what they meant by sleep disturbance in the context of HIV.…”
Section: Study Characteristics For Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymorphism rs3828942 corresponds to a variation in the intron domain of the LEP gene. This polymorphism has nevertheless been repeatedly shown to be associated with clinical CNS-related phenomena [44][45][46][47]. Therefore, it may be shown that this polymorphism itself, or a polymorphism with rs3828942 in equilibrium, has functional consequences.…”
Section: Discussionmentioning
confidence: 99%